2004
DOI: 10.1093/jnen/63.7.686
|View full text |Cite
|
Sign up to set email alerts
|

P2X7Receptor Expression after Ischemia in the Cerebral Cortex of Rats

Abstract: Large amounts of adenosine 5'-triphosphate (ATP) released from cellular sources under pathological conditions such as ischemia may activate purinoceptors of the P2X and P2Y types. In the present study, the expression of the P2X7 receptor-subtype in the brain cortex of spontaneously hypertensive rats was investigated using a permanent focal cerebral ischemia model. Immunocytochemistry with antibodies raised against the intracellular C-terminus of the P2X7 receptor showed a time-dependent upregulation of labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
175
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(187 citation statements)
references
References 55 publications
8
175
0
4
Order By: Relevance
“…Consistent with this hypothesis an increase in P2X7R immunoreactivity has been observed in activated microglia of two transgenic models of Alzheimer's disease [71,72] in microglia/ macrophages of spinal cord undergoing multiple or amyotrophic lateral sclerosis [73], in ischemic cortical tissue [74], and in a model of kainite-induced seizures [62] suggesting that microglial P2X7R, together with P2X4R, might be a general mediator of stress during pathological states. Besides uptake and release of inflammatory molecules, other pathways might contribute to microglial effects on neuronal excitability and disease outcome.…”
Section: Pathological Role Of P2x7r In Spinal Cordmentioning
confidence: 59%
“…Consistent with this hypothesis an increase in P2X7R immunoreactivity has been observed in activated microglia of two transgenic models of Alzheimer's disease [71,72] in microglia/ macrophages of spinal cord undergoing multiple or amyotrophic lateral sclerosis [73], in ischemic cortical tissue [74], and in a model of kainite-induced seizures [62] suggesting that microglial P2X7R, together with P2X4R, might be a general mediator of stress during pathological states. Besides uptake and release of inflammatory molecules, other pathways might contribute to microglial effects on neuronal excitability and disease outcome.…”
Section: Pathological Role Of P2x7r In Spinal Cordmentioning
confidence: 59%
“…P2X7 receptors were primarily localised along astrocyte processes in the hippocampus [14], while P2X7 receptors were observed on the bodies of GFAP-labelled reactive astrocytes in the nucleus accumbens after mechanical damage, but no labelling was detected on the processes [16]. In the cerebral cortex after ischaemia, P2X7 receptor immunoreactivity was equally present on cell bodies and processes of astrocytes [17]. In our study, astrocytes were harvested from the ventral portion of the midbrain.…”
Section: Discussionmentioning
confidence: 64%
“…Immunocytochemical studies have shown the localisation of P2X7 receptor subunits on astrocytes in various hippocampal subregions [14], in the cerebellum [15], in the nucleus accumbens after mechanical damage [16] and in the cerebral cortex after ischaemia [17]. In the latter two brain regions, P2X7 receptors were localised in GFAPlabelled reactive astrocytes [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after ischemia, the cerebral blood flow dramatically decreases in the ischemic core, leading to rapid energy failure, ATP depletion, ionic imbalance, and neuronal death [1] . The cells in the penumbra (tissues surrounding the ischemic core), however, can retain their activity for a prolonged period.…”
Section: Introductionmentioning
confidence: 99%
“…Seven distinct ionotropic P2X (P2X [1][2][3][4][5][6][7] and eight distinct metabotropic P2Y receptor subunits (P2Y 1,2,4,6,[11][12][13][14], classified by electrophysiological properties and their amino-acid sequence homology, have been cloned from mammals [4] .…”
Section: Introductionmentioning
confidence: 99%